EMC Focused Half-Bridge Characterization and Modeling - Dobusch, Julian; Konarski, Philipp; Kübrich, Daniel; Dürbaum, Thomas (EMC Europe 2019 - 2019 International Symposium on Electromagnetic Compatibility, 2019)
Power electronic circuits are a major source of Electromagnetic Compatibility (EMC) problems. The increased switching speed of modern semiconductor devises based on Silicon Carbide (SiC) and Gallium Nitride (GaN) further aggravates this issue. Thus, the importance of including EMC aspects in the design phase of a power electronic circuit is high and a reliable simulation model is very useful for rapid circuit testing and identification of the source of interference. However, the influence of parasitic components represents a crucial part of the coupling paths and thus has to be considered. This paper covers the development of a highly accurate simulation model including these parasitics. A major concern is the measurement of coupling capacitances which form an essential contribution to the model.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Electromagnetic Compatibility; Half-Bridge; Parasitic Components; Power Electronics